2017
DOI: 10.1515/fca-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

The Chronicles of Fractional Calculus

Abstract: Since the 60s of last century Fractional Calculus exhibited a remarkable progress and presently it is recognized to be an important topic in the scientific arena. This survey analyzes and measures the evolution that occurred during the last five decades in the light of books, journals and conferences dedicated to the theory and applications of this mathematical tool, dealing with operations of integration and differentiation of arbitrary (fractional) order and their generalizations.MSC 2010 : Primary 26A33; 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 133 publications
1
58
0
2
Order By: Relevance
“…In 1860s, Riemann and Liouville obtained now celebrated definitions of fractional operators, by extending the Cauchy integral formula. Such fractional operators have a major role in practical problems [3]. In particular, Heymans and Podlubny have shown that it is possible to attribute a physical meaning to initial conditions expressed in terms of Riemann-Liouville fractional derivatives on the field of viscoelasticity, which is more appropriate than standard initial conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 1860s, Riemann and Liouville obtained now celebrated definitions of fractional operators, by extending the Cauchy integral formula. Such fractional operators have a major role in practical problems [3]. In particular, Heymans and Podlubny have shown that it is possible to attribute a physical meaning to initial conditions expressed in terms of Riemann-Liouville fractional derivatives on the field of viscoelasticity, which is more appropriate than standard initial conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Cauchy-type problem for equation (31), in which the initial condition is given at the time τ = 0 by A(0), has solution that can be represented in the form…”
Section: Violation Of Semi-group Property: Non-markovian Dynamicsmentioning
confidence: 99%
“…An effective and powerful tool for describing memory effects is the fractional calculus of derivatives and integrals of non-integer orders [22,23,24,25,26]. These operators have a long history of more than three hundred years [27,28,29,30,31]. We should note that the characteristic properties of fractional derivatives of non-integer order are the violation of standard rules and properties that are fulfilled for derivatives of integer order [32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…However, upon experimentation on a low-power 415-V permanent magnet synchronous motor (PMSM) used in a high-rise elevator, it was discovered that the insulation resistance dynamics do not follow (1.4) nor (1.5). In fact, upon using fractional calculus [24,27], it was assumed that the model should appropriately follow the fractional-order transfer function (FOTF)…”
Section: Thermal Class Rating Minimum Pimentioning
confidence: 99%